The influence of financial literacy on student spending habit at UiTM Malacca City Campus / Mohamad Faiz Syafiq Abdullah - Abdullah, Mohamad Faiz Syafiq (Faculty of Office Management and Technology, 2016)
The objective of the study is to identify the relationship between financial literacy on student spending habits. There are three thing can be influence financial literacy on student spending habits which is financial attitude, financial knowledge and family influence. The study was conducted at UiTM Malacca Campus City and the researcher used questionnaire as the tools to find out the result from the respondent at UiTM Malacca Campus City. The respondents are student International Business from Faculty Business Management. Besides that, the researcher had explained about what is the relationship between financial literacy and student spending habit. moreover, the researcher explained factor of financial literacy that influences student spending habits in UiTM Malacca. Meanwhile, the researcher defined the level of spending habit among higher education student.